"Our people has got to come to terms with that": changing perceptions of the digital rectal examination as a barrier to prostate cancer diagnosis in African‐Caribbean men. Issue 10 (14th September 2016) - Seymour‐Smith, Sarah; Brown, David; Cosma, Georgina; Shopland, Nicholas; Battersby, Steven; Burton, Andy
Abstract: Objective: African‐Caribbean men in the United Kingdom in comparison with other ethnicities have the highest incidence rate of prostate cancer. Psychosocial aspects related to screening and presentation impact on men's behavior, with previous studies indicating a range of barriers. This study explores one such barrier, the digital rectal examination (DRE), due to its prominence within UK African‐Caribbean men's accounts. Methods: African‐Caribbean men with prostate cancer (n = 10) and without cancer (n = 10) were interviewed about their perceptions of DRE. A synthetic discursive approach was employed to analyze the data. Results: Findings illustrate that an interpretative repertoire of homophobia in relation to the DRE is constructed as having an impact upon African‐Caribbean men's uptake of prostate cancer screening. However, the discursive focus on footing and accountability highlight deviations from this repertoire that are built up as pragmatic and orient to changing perceptions within the community. Conclusions: Health promotion interventions need to address the fear of homophobia and are best designed in collaboration with the community.